1980
DOI: 10.1007/bf01011931
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme histochemical studies on the conducting system of the human heart

Abstract: In this communication, the results of applying various histochemical techniques for the localization of oxidoreductases, transferases, hydrolases and isomerases in the human heart are presented. The Purkinje fibres of the atrioventricular conducting system of the human heart differ from the myocardium proper in containing a slightly higher activity of most of the glycolytic and gluconeogenetic enzymes investigated. The relatively higher activity of 6-phosphofructokinase, the key enzyme in anaerobic carbohydrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1982
1982
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…The abundance of this enzyme in the prenatal compared to the postnatal heart has also been established biochemically (Henderson, 1977). In comparing our results with reports that claim that the adult conduction system is rich in AChE activity (Elias et al, 1980) it has to be kept in mind that we only describe AChE activity in myocytes. It is not always clear whether the rich nerve supply of the definitive conduction system (James and Spence, 1966;Moravic and Moravic, 1984) is taken into account.…”
Section: Discussionsupporting
confidence: 65%
“…The abundance of this enzyme in the prenatal compared to the postnatal heart has also been established biochemically (Henderson, 1977). In comparing our results with reports that claim that the adult conduction system is rich in AChE activity (Elias et al, 1980) it has to be kept in mind that we only describe AChE activity in myocytes. It is not always clear whether the rich nerve supply of the definitive conduction system (James and Spence, 1966;Moravic and Moravic, 1984) is taken into account.…”
Section: Discussionsupporting
confidence: 65%
“…4). that the oxygen uptake and the activity of succinate dehydrogenase were much lower in the conduction system whereas the glycogen concentration was higher than in the working myocardium (SNIJDER and MEIJER, 1970;MEIJER and DEVRIES, 1978;ELIAS et al, 1980ELIAS et al, , 1982TsuYUGUCHI et al, 1980;THERY et al, 1985). These data suggest that the conduction system may depend more on glycolysis for energy supply than does the working myocardium, and that it is more resistant to anoxic damages.…”
Section: Resultsmentioning
confidence: 99%
“…The same has also been described for the conducting system in man (Thery eta]., 1985). Elias et al (1980), however, found no significant differences in LDH activity between the different types of human cardiac cells.…”
Section: Discussionmentioning
confidence: 82%
“…Earlier studies carried out by means of qualitative histochemistry also led to confusing results. Thus, the specialized muscle cells of the conducting system were found to manifest lower succinate dehydrogenase activity in comparison with the other cardiac muscle cells (Schiebler, 1962;Schiebler & D6rr, 1963;Otsuka eta]., I967; Snijder & Meijer, 1970;Elias et al, 1980). From this it was concluded that the conducting system is provided with only weak capacity for oxidative energy metabolism, but with a higher activity of the enzymes of anaerobic glycolysis.…”
Section: Introductionmentioning
confidence: 90%